Ética, bioética y los desafíos del siglo XXI - Freitas Drumond, José Geraldo de (Pontificia Universidad Católica del Perú. Fondo Editorial, 2012)
The contemporary world is characterized by a formidable accumulation of scientific knowledge, which is responsible for developing the technology that permeates all latitudes of the planet and is incorporated, so virtually irreplaceably, to the daily life of human beings. However, the world is in a borderline: serious responsibilities determined by the process of increasingly aggressive human intervention in the biosphere (accelerating its deterioration) and the very human biology, reaching its genetic identity. Humanity is wrapped in a moral dilemma, since it is found that most of the benefits offered by human knowledge —the whole set of scientific and technological progress of humanity— remains inaccessible to most of the universal family. A recurring issue in today’s society is to establish the boundaries between normal and abnormal, between natural and artificial. Is the human being willing, once again, to transgress the parameters established by her concerning what is normal, anatomically and physiologically? Will she not be satisfied by merely making her biological structure sufficiently adapted to the current practices of the species? Will she want more? In the singular historical transition experienced by contemporary society, the emergence of a new ethical reflection to modulate human behavior has become imperative, so that the actions of men and women can converge to the achievement of universal benefits, so as not to endanger the very survival of human beings on the planet.

El mundo contemporáneo se caracteriza por un magnífico conjunto de conocimientos científicos que son responsables por el desarrollo de la tecnología que se disemina en todas las latitudes del planeta y se incorpora, de modo prácticamente permanente, en la cotidianidad del ser humano. Sin embargo, el mundo se encuentra en una frontera de graves responsabilidades determinadas por el proceso de intervención humana cada vez más agresiva en la biósfera (acelerando su deterioro) y en la propia biología humana, alcanzando su identidad genética. La humanidad se encuentra ante una encrucijada moral, al constatarse que la mayoría de las conquistas propiciadas por el conocimiento humano —todo el conjunto del progreso científico y tecnológico de la humanidad— permanece inaccesible para la mayoría de la familia universal. La cuestión recurrente en la sociedad actual es establecer los límites entre lo normal y lo anormal, entre lo natural y lo artificial. ¿Estará el hombre dispuesto, una vez más, a transgredir los parámetros de normalidad anatómica y fisiológica establecidos por él mismo? ¿No le bastará para estar satisfecho el tener su estructura biológica suficientemente adaptada a las prácticas corrientes de la especie? ¿Habrá de querer más? En la singular transición histórica vivida por la sociedad contemporánea se hizo imperativo el surgimiento de una nueva reflexión ética para modular el comportamiento humano, de modo que las acciones de los hombres y las mujeres puedan converger para la consecución de beneficios universales, sin poner en riesgo la propia supervivencia de los seres humanos en este planeta.
Ethics and bioethics concerning challenges in the 21st Century
Keywords: Ética; Bioética; Conducta moral ante los desafíos del siglo XXI; Procedimientos biotecnológicos en los seres humanos; https://purl.org/pe-repo/ocde/ford#5.05.00